The legal consequences of the criminal acts signature in the deed of land purchase in front of the land deed official - Wim Fadel Azmilhuda (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Everyone needs evidence regarding a right and an event that occurred. In practice, the Official for Making Land Deeds is an official who is given the authority by government regulations to make authentic deeds. An authentic deed is a proof that is perfect, complete and binding, so that the truth of the things written in the deed must be acknowledged for its truth. An authentic deed contains statements from the parties which are used as the basis for making an authentic deed. Problems arise when the contents of the deed are not in accordance with reality, because there are parties who falsify the signatures in the Sale and Purchase Deed made by the PPAT. The research in this article is normative by using literature studies, documents studies, studies and existing decision studies. With this research, it is hoped that we can find out the legal consequences of forging signatures in the land sale and purchase deed and find out the legal remedies that can be taken when carrying out fake signatures in the land sale and purchase deed.